1999
DOI: 10.1007/s00276-999-0087-9
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic guidelines for the prevention of abdominal wall hematoma induced by trocar placement

Abstract: A knowledge of the parietal structures of the abdominal wall is necessary to minimize risks of operative procedures like laparoscopy. For means to prevent intraoperative bleeding and the occurrence of abdominal wall hematoma, we studied the course of the inferior epigastric arteries and the ascending branch of the deep circumflex iliac artery in 21 human cadavers. The abdominal wall structures were dissected and the distances of the arteries in relation to anatomic structures such as the umbilicus, pubic symph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…An anatomical study of 21 cadavers, in which the course of the inferior epigastric arteries and the ascending branches of the deep circumflex iliac artery was pursued, showed that half of the 36 trocar insertion sites recommended in the common literature imply the risk of injury to these arteries. Therefore, the authors suggested the following insertion sites: ventral midline, and in a zone of 5-cm width lateral to the lateral border of the rectus sheath [22]. Another important anatomical relationship is the distance between the skin and the retroperitoneal vascular structures at the level of the umbilicus, which can be reduced to less than 2 cm, particularly in thin anaesthetised patients with muscle relaxation [23].…”
Section: Discussionmentioning
confidence: 98%
“…An anatomical study of 21 cadavers, in which the course of the inferior epigastric arteries and the ascending branches of the deep circumflex iliac artery was pursued, showed that half of the 36 trocar insertion sites recommended in the common literature imply the risk of injury to these arteries. Therefore, the authors suggested the following insertion sites: ventral midline, and in a zone of 5-cm width lateral to the lateral border of the rectus sheath [22]. Another important anatomical relationship is the distance between the skin and the retroperitoneal vascular structures at the level of the umbilicus, which can be reduced to less than 2 cm, particularly in thin anaesthetised patients with muscle relaxation [23].…”
Section: Discussionmentioning
confidence: 98%
“…8 Iatrogenic hematomas from injuries to the deep circumflex iliac artery as a result of trocar placement during laparoscopic surgery have also been reported in recent years. 9,10 Predisposing factors for spontaneous hemorrhage of the abdominal wall include the following factors: (a) overcontraction or overstretching of the muscle as a result of coughing, sneezing, straining, twisting, vomiting, etc. ; (b) weakness of the vessel wall or decrease in muscular resistance as a result of hypertension, arteriosclerosis, old age, obesity, pregnancy, previous surgery, trauma, inflammatory disease, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, for the left hypochondrium puncture one must take into account the risk of injury to the superior epigastric vessels and structures immediately posterior to the anterior abdominal wall at the puncture site, such as the gastric body, transverse colon and greater omentum. However, the trunks and branches of larger caliber of the superior epigastric vessels never lie at a distance greater than eight centimeters from the midline of the abdomen, so punctures beyond that distance prevent lesions of those vessels [21][22][23] . The values of tests and parameters established to assess the safety in the development of pneumoperitoneum has been shown by Azevedo [16][17][18] in patients without previous abdominal surgeries, previous intra-abdominal inflammatory conditions and with a BMI below 30.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%